Tumor Volume Regression during and after Radiochemotherapy: A Macroscopic Description - Castorina, Paolo; Ferini, Gianluca; Martorana, Emanuele; Forte, Stefano (Journal of personalized medicine, 2022)
Tumor volume regression during and after chemo and radio therapy is a useful information for clinical decisions. Indeed, a quantitative, patient oriented, description of the response to treatment can guide towards the modification of the scheduled doses or the evaluation of the best time for surgery. We propose a macroscopic algorithm which permits to follow quantitatively the time evolution of the tumor volume during and after radiochemotherapy. The method, initially validated with different cell-lines implanted in mice, is then successfully applied to the available data for partially responding and complete recovery patients.
Keywords: biophysics; radiotherapy; oncology; complex systems